Effect of Seasonal Variation on Physicochemical Properties of Shallow Groundwater in a Typical Basement Complex Terrain of Nigeria - Ige, Olusegun O.; Oredipe, Ifeoluwa M.; Ogunsanwo, Olufemi (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2015)
Analyses of Sixty-nine (69) groundwater samples have been carried out. This was aimed at evaluating major ions andtheir origin; establishing hydro-chemical facies and determining the suitability of groundwater in a typical basementcomplex terrain for drinking and irrigation purposes. Hydrochemical analyses revealed ionic dominance in the orderof Ca2+>Mg2+ during the wet season and Ca2+>Mg2+>Na++K+ in the dry season. The pattern of dominance of themajor anions is HCO3->Cl->SO42- for both seasons which is an indication of change in seasonal effect. Physicalevaluation revealed that pH, turbidity and colour are higher in order of degree of pollution at the wet season than dryseason while other parameters are higher during dry season. The hydrochemical facies of groundwater during dryseason were found to be CaHCO3, (Ca+Mg)Cl, CaCl and NaCl while only CaHCO3 and (Ca+Mg)Cl are presentduring wet season. The source of the ions in the waters were examined and classified accordingly as rock weatheringdominance. Correlation exists among major cations and Total Dissolved Solid with average positive correlationcoefficients of 0.71 and 0.49 for wet and dry seasons respectively, which is a clear indication of the contribution ofthese ionic components to the overall mineralization. Results however showed that the water resources are suitable fordrinking and irrigation as at the time of study when compared with Standards.